Factors associated with sports talent detection in school’s physical education classes in China - Xiang, Changqing (2024)
The pedagogical objectives of the Chinese school physical education, set the foundation for detecting and cultivating sports talent. This became one of the main objectives of the school physical education curriculum, as it serves as a crucial driving force to promote sports development in China. The initial stage of sports talent cultivation involves various factors that will influence sports talent detection. These factors are crucial for the identification, training quality, and achievement of competition performance of athletes in the later stage. The objective of this research was to identify factors influencing talent detection in school physical education classes. These factors are crucial in sport talent search for potential elite athletes and to promote the development of China’s sports industry. Three different instruments were used in this study which was: 1) A survey on students’ participation in school physical activities, with a sample size of 578 (male=296, female=282); 2) A survey regarding the situation of sports talents detection in school physical education classes, with a sample size of 150 (male=83, female=67); 3) A questionnaire on the factors that affect the detection of school sports talents which targets physical education teachers coaches, and sports administrators, with a sample size of 420 (male=239, female=181). Subjects were recruited from the Guangdong and Hubei Province in China. A pilot study and an exploratory factor analysis on the items were conducted before the final questionnaire and survey forms were distributed. Meanwhile, the influencing factors in talent detection were validated and analysed. Multiple regression analysis was also conducted to investigate the relationship between the sports talent detection and the influencing factors related to it. The results show that the current detection of sports talent in China school’s physical education classes still faces challenges, and physical education teachers have different standards and perceptions when conducting talent detection. The duration of students participating in school physical activities was low (62.46% of students participate in activities lasting 30 minutes to 1 hour only per week). This contributes to the low frequency of student’s participation in sports activities (2-3 times per week - 52.77%) resulting in fewer talented students being detected by the physical education teachers. Six factors were found to have a significant impact on the detection of school sports talent. These factors ranked from highest to lowest are: 1) family characteristics (23.48%); 2) psychological traits (19.07%); 3) social system (17.58%); 4) students’ physical conditions (15.06%); 5) physical education teachers (13.12%), and 6) school environment (11.69%). Of all the factors, family characteristics (+0.424) and school environment (+0.291) were the two biggest predictors of sports talent detection. In conclusion, the Ministry of Education of China may consider the critical influencing factors of talent detection in school physical education classes and can be included in the planning of future physical education curriculum to lay the foundation for better talent detection. From this research, among the important suggestions are: 1) Early sports talent detection; 2) Form a well-developed sports talent detection system; 3) Focus on developing students’ sports expertise. Hence, through these ways, China can accelerate the country’s sports development and construction of a leading sports nation.